System delays and target points: analysis of STEMI response program a single center. (25th January 2023) - Toledano, B; Garganera, K B; Prado, J P; Sabas, M L; Martinez, G S
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: STEMI carries the highest risk among the AMI and the mortality is influenced by many factors. Hospital delays are the most easily audited and should be analyzed and improved. Methodology: Participants were adults aged > 19 years enrolled in the AMI registry due to STEMI and treated with emergency PCI from January 2019 to June 2021. The door-to-balloon times and STEMI diagnosis-to-wire cross times were divided into Met and Unmet groups and time frames were compared using the Mann Whitney U test. For time frames with no significant difference, the median of the Met group was adopted while in time frames with a significant difference, the optimal target points were chosen from the highest percentages of Met if ≤ and Unmet if > the target point. Odds ratio (OR) with 95% confidence intervals from binary logistic regression were done to predict the Met status. Results: A total of 113 participants were analyzed. Significant delays were seen in ECG-Paging (p=<0.034), CFOD arrival-to-STEMI diagnosis (p=0.008), STEMI diagnosis-to-consent (p= <0.001), consent-to-Cath lab (p=<0.001) and Cath lab-to-puncture (p=0.003). The optimal targets in minutes: Door-ECG (median 9), ECG-Paging (≤1/>, 56.67%, 62.65%, OR 2.19, p=0.069), paging-to-CFOD arrival (median <2), CFOD arrival-to-STEMI diagnosis ( ≤/>3, 66.67%, 51.81% OR 2.15, p=0.086), STEMI diagnosis-to-consent (≤/>10, 78.26%, 67.78%, OR 7.57, p=<0.001), consent-to-Cath lab (≤/>24, 73.91%, 67.78%, OR 15.38, p=<0.001), Cath lab-to-puncture (≤/>12, 65.22%, 58.89%, OR 2.68, p=<0.043). Conclusion: In a developing country and during the COVID-19 pandemic, the most significant delays of our STEMI program occurred in obtaining consent for emergency percutaneous coronary intervention and transferring the patient to the catheterization laboratory. Optimal target points for every time frame can provide concrete objectives that may increase the chance of achieving the door-to-balloon and STEMI diagnosis-to-wire cross goals. Comparison of profile and time frames Optimal target points & team members